Material strength evolution of FCC metals under high strain rates - Gilroy-Hirst, Caitlin (Cranfield University, 2020)
Copper and stainless steel 21-6-9, two face-centred cubic (FCC) materials, were shock loaded in partially recovered uniaxial strain flyer-plate impact experiments at varying impact pressures (6 GPa - 16 GPa). These samples were collected post impact via three differing recovery configurations: (1) standard or ‘free boundary’; (2) partial shock recovery, i.e. using both ‘momentum trapping’ and ‘soft recovery’ techniques but with a flyer plate thickness of 10 mm to see the effects on partial tensile release in the rear spall plates of an established recovery target design; finally (3) a traditional full recovery comparison with a 2 mm flyer impact. These samples were then analysed using a suite of analytical techniques including X ray diffraction, optical microscopy, hardness testing and compression after impact testing, to observe the material deformation characteristics in the simplified partially recovered shock and release condition compared to the more complex ‘standard’ release wave situation. A control sample of a ‘ fully recovered’ sample was also carried out for comparative purposes. The rear spall plates were modified on these partially recovered samples to see the effect that this had on the tensile release waves and how this changed the material deformation properties overall. Results for the stainless steel 21-6-9 demonstrated the ability of the partial shock recovery technique (hereafter called ‘partial-recovery’) to mitigate the reverberations compared to that of the standard samples. Upon analysis of the targets, it was observed that the dislocation density was generally lower for the partially recovered samples but varied with impact pressure for both the standard and recovered configuration. For the stainless steel recovery experiments an increasing dislocation density from 4 x 1015 m-2 at 6 GPa to 6.5 x 1015 m-2 at 12 GPa was observed which then decreased to 5.5 x 1015 m-2 at 16 GPa. The twinning density to grain ratio obtained from optical microscopy showed a linear increase (y= 1.5345x - 8.3508) with an R2 value of 0.8295 from 7 GPa at 4 twins per grain to 17 twins per grain at 16 GPa. Twinning density is indicative of a successful recovery, where a successful recovery is a reduction in reverberations in the sample and in a full recovery is a 1D shock. The dataset both verifies the use and success of the recovery technique as well as demonstrating the materials characteristics under partial-recovery, while observing reverberation effects.
© Cranfield University 2020. All rights reserved. No part of this publication may be reproduced without the written permission of the copyright owner
Keywords: Shock physics; Material deformation